Evaluating the effectiveness of anti-crisis state aid measures - Burger, Anže (Teorija in praksa, 2020)
This methodological contribution is explaining selected empirical methods useful for evaluating the effectiveness of state aid measures in order to separate the causal effect from the effect due to non-random assignment of the treatment. These methods were employed in the analysis of the Effectiveness of Slovenia%s Anticrisis State Aid Measures During the Great Recession. Methodological note is complementary to of the article entitled %What Can Be Learnt from the Effectiveness of Slovenia%s Anti-crisis State Aid Measures During the Great Recession: Application to the Covid-19 Downturn%. First, we explain the propensity score matching (PSM) method, followed by difference-in-differences regression (DiD). Finally, we discuss the value of using both methods and include some auxiliary tables and figures
Keywords: Covid-19; Crises; Economic policy; Ekonomska politika; ekonomski ukrepi; Epidemics; Epidemije; Krize; metoda prirejanja na podlagi ocenjene verjetnosti; metoda regresija razlike v razlikah; protikoronski ukrepi; protikrizni ukrepi; učinki protikriznih ukrepov